Modernity and technology a philosophical investigation of Martin Heidegger and Bruno Latour - Riis, Søren (Lexington Books, 2025)
"Bruno Latour and Martin Heidegger seem like opposite thinkers, but in tandem they can in fact help us avoid some of the most profound perils of our time. Their understandings of modernity and technology offer a number of interwoven insights that may demolish dangerous dogmas and lead to new hope"--
Keywords: Technology / Philosophy; Technology / Social aspects; Civilization, Modern / Philosophy; Heidegger, Martin / 1889-1976; Latour, Bruno; Technologie / Philosophie